Technical actions, heart rate, and locomotor activity in 7v7 and 8v8 games for female youth soccer players - Oerntoft, C.; Larsen, M. N.; Andersen, T. B.; Rasmussen, L. S.; Póvoas, S. C. A.; Randers, M. B.; Krustrup, P. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to evaluate technical performance, heart rate (HR), and activity profile in 7v7 and 8v8 soccer games for 9- to 10-year-old girls (U11). A total of 24 female youth players participated in the study, all playing 20-minute 7v7 and 8v8 games with 160 and 223 m2 per player, respectively. Technical actions, HR, and activity profile were measured during the games using video filming, HR monitors, and 5-Hz Global positioning system (GPS) units. The number of technical actions was higher in 7v7 than in 8v8 games (34 ± 19 vs. 28 ± 14; p = 0.03; d = 0.37), as was the number of successful actions (25 ± 16 vs. 20 ± 12; p = 0.01; d = 0.35), with no difference in success rate for technical actions (70 ± 13 vs. 69 ± 14%; p = 0.63; d = 0.07). No differences were found between 7v7 and 8v8 in total distance covered (1,574 ± 251 and 1,622 ± 281 m; p = 0.66; d = 0.18), peak speed (19.5 ± 2.6 and 20.7 ± 1.5 km·h-1; p = 0.16; d = 0.56), mean HR values (85 ± 5 and 86 ± 6%HRpeak; p = 0.85; d = 0.18), and time of >90% HRpeak (37 ± 16 and 35 ± 14% of playing time; p = 0.70; d = 0.13). Distance covered at the highest running speeds of >16 km·h-1 was lower in 7v7 than in 8v8 games (34 ± 24 vs. 63 ± 34 m; p = 0.018; d = 0.98), as was the number of entries into this speed zone (8 ± 5 vs. 13 ± 7; p = 0.006; d = 0.82). In conclusion, more technical actions and successful actions were observed in 7v7 than in 8v8 games, but players covered more ground with high-speed running in 8v8 games. This study also revealed that HR values were high in both game formats for U11 adolescent female players, with no difference between formats.